2018
DOI: 10.3390/ijms19041067
|View full text |Cite
|
Sign up to set email alerts
|

Novel (1E,3E,5E)-1,6-bis(Substituted phenyl)hexa-1,3,5-triene Analogs Inhibit Melanogenesis in B16F10 Cells and Zebrafish

Abstract: The present study aimed to evaluate the anti-melanogenic activity of 1,6-diphenyl-1,3,5-hexatriene and its derivatives in B16F10 murine melanoma cells and zebrafish embryos. Twenty five (1E,3E,5E)-1,6-bis(substituted phenyl)hexa-1,3,5-triene analogs were synthesized and their non-cytotoxic effects were predictively analyzed using three-dimensional quantitative structure-activity relationship approach. Inhibitory activities of these synthetic compounds against melanin synthesis were determined by evaluating mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…After allowing to recover for additional 24 hr, the cells were harvested by Trypsin‐EDTA solution (Welgene, Gyeongsan, South Korea). Fractionation of nuclear and cytoplasmic proteins from the collected cells was performed by employing the NE‐PER ® Nuclear and Cytoplasmic Extraction Reagents (Thermo Fisher Scientific, Rockford, IL, USA) as previously described (Oh et al., ). The protein quantities in both cytoplasmic and nuclear fractions were determined by Bradford assay (Bio‐Rad Protein Assay, Bio‐Rad, Hercules, CA, USA) through the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…After allowing to recover for additional 24 hr, the cells were harvested by Trypsin‐EDTA solution (Welgene, Gyeongsan, South Korea). Fractionation of nuclear and cytoplasmic proteins from the collected cells was performed by employing the NE‐PER ® Nuclear and Cytoplasmic Extraction Reagents (Thermo Fisher Scientific, Rockford, IL, USA) as previously described (Oh et al., ). The protein quantities in both cytoplasmic and nuclear fractions were determined by Bradford assay (Bio‐Rad Protein Assay, Bio‐Rad, Hercules, CA, USA) through the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained three layers were then tested for antimelanogenesis activity in murine melanoma B16-F10 cells. The mouse B16 melanoma cell is a sensitive, reliable, and feasible platform for screening large number of small molecular melanogenesis regulators [23,24,25]. At the concentrations of 25–100 μg/mL, the ethyl acetate-soluble layer demonstrated the most potent inhibitory activity, while slight inhibition was observed for either the n -butanol or water-soluble layers (Figure 1A) as evidenced by melanin contents in lyzed B16-F10 melanoma cells (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…We found that carvone decreased melanin content in a concentration-dependent manner ( Figure 1B,C). We recently conducted a phenotype-based approach to screening for compounds in B16F10 melanoma cells to find small-molecule inhibitors of melanin synthesis [16,17]. By this method, we found that carvone treatment markedly decreases melanin content.…”
Section: Carvone Decreases Melanin Content Of B16f10 Melanoma Cellsmentioning
confidence: 99%